Obtain the inverse Laplace transform of t cos pt, p is not equal to 0.
"F(t)=tcos(pt),p\\neq0\\\\\n\\therefore \\mathcal{L}^{-1}\\{F(s)\\}\\\\\n=\\frac{d}{dt}\\left(\\mathcal{L}^{-1}\\left\\{\\cos \\left(ps\\right)\\right\\}\\right)+\\mathcal{L}^{-1}\\left\\{\\cos \\left(ps\\right)\\right\\}\\left(0\\right)"
Now "\\mathcal{L}^{-1}\\left\\{\\cos \\left(ps\\right)\\right\\} : No \\; solution \\;for\\; standard \\; function"
"\\mathcal{L}^{-1}\\{F(s)\\}" has no solution.
Now for Laplace transform,
"F(t)\\\\\n=tcos(pt)\\\\\n=\\frac{1}{2p}2pcos(pt)\\\\\n=\\frac{1}{2p}\\left[(sin(pt)+pcos(pt))-(sin(pt)-ptcos(pt))\\right]"
"\\\\\\;\\\\\n\\therefore \\mathcal{L}\\{F(t)\\}\\\\\n=\\mathcal{L}\\left(\\frac{1}{2p}\\left[(sin(pt)+pcos(pt))-(sin(pt)-ptcos(pt))\\right]\\right)\\\\\n=\\frac{1}{2p}\\left[\\mathcal{L}(sin(pt)+pcos(pt))-\\mathcal{L}(sin(pt)-ptcos(pt))\\right]\\\\\n= \\frac{1}{2p}\\left[\\frac{{2p{s^2}}}{{{{\\left( {{s^2} + {p^2}} \\right)}^2}}}-\\frac{{2{p^3}}}{{{{\\left( {{s^2} + {p^2}} \\right)}^2}}}\\right]\\\\\n=\\frac{1}{2p}\\times \\frac{{2ps^2-2{p^3}}}{{{{\\left( {{s^2} + {p^2}} \\right)}^2}}}\n=\\frac{1}{2p}\\times \\frac{{2p(s^2-p^2)}}{{{{\\left( {{s^2} + {p^2}} \\right)}^2}}}\\\\\n=\\frac{s^2-p^2}{(s^2+p^2)^2}"
Therefore, Laplace transform of "\\pmb{F(t)=\\frac{s^2-p^2}{(s^2+p^2)^2}}" .
Comments
Leave a comment